Entrance to the Jain Temple Complex - Temples of India Project Team (Jio Institute, 2024)
Seen here is the north-facing principal entrance of the Jain temple complex. The temple is situated on a raised platform which can be accessed by a flight of steps. The entrance is marked by pillar remains on four corners which must have supported a semi-open pavilion that was connected to the raised platform of the temple complex.